Study of Track Quality Index (TQI) by using EM140 and KRAB 10 for Electrified Double Track Project (EDTP) Gemas to Johor Bahru - Yussob, Nurul Hafizah; Abd Latif, Muhamad Faiz; Mohamed Jizi, Siti Zarini (Progress in Engineering Application and Technology, 2023)
Track geometry, which includes parameters like alignment, rail surface, twist, cant, and gauge, is important in determining track quality and safety particularly for high-speed trains. The traditional approach of track maintenance, on the other hand, frequently depends on manual or static inspections, which can lead to potential inaccuracies, restricted coverage, and costly corrective actions. This study aims to address these challenges by developing and validating a track quality index (TQI) that incorporates both static and dynamic measurement techniques especially EM140 track recording car as a model in the Electrified Double Track Project (EDTP) Gemas to Johor Bahru. The TQI will enable a data-driven approach to track maintenance, facilitating proactive interventions, optimizing resources, and ensuring the long-term sustainability and safety of railway track. Through a comprehensive understanding of the TQI concept and its practical applications in this research, advanced measurement technology like the EM140 track recording car enables timely detection of any deviations or defects.